Ruptura amorosa y su incidencia en la salud mental de una joven de 25 años del cantón Urdaneta - Icaza Vera, Lisbeth Andreina (2023)
This case study focused on a 25-year-old female patient, who manifests a process of love breakup which affects her mental health, considering one of the phases that can cause a lot of pain in the face of the loss of a loved one. The presence of depressive symptoms and dissatisfaction with life can be one of the consequences generated by this separation process, which is why this study was developed with a type of descriptive though qualitative approach, the techniques used for the development of the case was the observation sheet , the semi-structured interview, clinical history and psychometric tests corresponding to the problem such as the Beck Depression Inventory and the Emotional Dependency Inventory which provided important information for the elaboration of a presumptive diagnosis. Complying with the criteria of the DSM-V as it was 296.21(F320.) Mild Depression. Under this diagnosis, a therapeutic scheme was carried out with cognitive behavioral therapy as the most efficient for the psychological approach, which developed therapeutic techniques such as psychoeducation, cognitive restructuring, examination of evidence, role playing, schedule of activities, relaxation technique.